Prevalence of Victims and Perpetrators of Dating Violence Among Adolescents - Daffa Nazmatu Zahra; Muhammad Muhajirin (Edupotensia, 2025)
This study aims to identify and analyze the prevalence of dating violence among 11th-grade high school students in Banjar City. Utilizing a quantitative method with a descriptive design, the study involved a sample of 489 students. The instrument employed was the Conflict in Adolescent Dating Relationships Inventory (CADRI) based on Wolfe’s concept, which measures various dimensions of violence, including physical violence, threatening behavior, sexual violence, relational aggression, and emotional and verbal abuse. Results indicated that 91% of students fall into the low category as perpetrators, while 85.89% of victims also experience low levels of violence, characterized by milder forms of abuse. Further analysis revealed significant differences between male and female students in the emotional and verbal violence dimension, with female students exhibiting higher levels than male students. The study concludes that dating violence among high school students in Banjar City is generally low; however, attention through counseling services and education on healthy relationships remains necessary to prevent further escalation of violence.